MATHEMATICAL AND SOFTWARE TOOLS FOR OPTIMIZING THE GRAPE DRYING PROCESS (Academicia Globe: Inderscience Research, 2022)
One of the current scientific and practical work is the introduction of digital management technologies in the country and society.